Regulation of the Curator's Responsibility in Securing Bankrupt Assets to Fulfill Justice - Alipraja, Muhammad (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Bankruptcy of law is a law to arrange about bankruptcy with the intention to avoid being deception Creditors to get prerogative with sell goods from Debtor. Petition of bankruptcy submitted to The Commercial Court who be competent by their territory and after petition granted so that Debtor be avowed bankruptcy and taken over by Curator. However, during domination by Curator be found problem namely Curator cheating with obscure manner of bankruptcy estate, as a consequence prejudice for the parties with the result that affect of justice. Based on the above, the legal issues that will be discussed in this thesis are : 1) How is adjustment responsible of curator do safekeeping bankruptcy estate? 2) What weakness adjustment responsible of curator do safekeeping bankruptcy estate who involve injustice? 3) How should the adjustment responsible of curator do safekeeping bankruptcy estate to fulfill justice. The method used in this research is normative research. Based on the research, the conclusions are : 1) Adjustment responsible of curator do safekeeping bankruptcy estate not fulfill justice because there is no equality of rule so that rights and obligations not reached balance which raises disadvantage, 2) Weakness contained in adjustment who involve injustice namely, is not clearly regulated about adjustment responsible of curator, is not regulated about penalty provisions, and is not clearly regulated about oversight of curator by supervisory judge, and 3) Alternative deals for adjustment to fulfill justice namely, augment to Article 72 A points (1) until points (5) about adjustment of curator personally, augment to Article V about penalty provisions Article 299, and amendment to Article 98, Article 102. Article 116, and Article 201 about oversight of curator by supervisory judge.